Eliciting Reciprocal Peer-Tutoring Groups' Metacognitive Regulation Through Structuring and Problematizing Scaffolds. Issue 4 (1st October 2016) - De Backer, Liesje; Van Keer, Hilde; Valcke, Martin
Abstract : The study examines whether structuring (SS) versus problematising scaffolds (PS) differently affect reciprocal peer-tutoring (RPT) groups' adoption of particular regulation skills, deep-level regulation, and tutee-initiated regulation. A quasi-experimental design involving two experimental groups (SS versus PS condition) was adopted. The first, third, and sixth RPT-session of eight randomly selected RPT-groups (four from the SS condition, four from the PS condition) were videotaped (48hr). Mixed ANOVAs were conducted to investigate the impact of both scaffold types on RPT-groups' metacognitive regulation. The results indicate that neither scaffold type encourages RPT-groups into a balanced adoption of, or initiative for, regulation skills and a deep-level approach. Nevertheless, the PS condition significantly outperforms the SS condition in evoking deep-level monitoring, tutee-initiated orientation, and tutee-initiated monitoring.